MENINGKATKAN KINERJA UMKM MELALUI DIGITALISASI PRODUK USAHA PADA KELOMPOK USAHA MIKRO DI DESA MOTOBOI KECIL KOTA KOTAMOBAGU - Soegoto, Agus Supandi; Wenas, Rudy Steven; Wahab; Soeikromo, Deasy; Soegoto, Andini Pratiwi; Satria, Andi Wiratama (FEB Universitas Sam Ratulangi Manado, 2024)
MSMEs play an important role in national economic resilience because they can become independent businesses that can increase people's income and welfare. On the other hand, fierce competition in today's digital era has encouraged the community and MSME business actors to be able to compete and develop their businesses through product digitization and business promotion. Advances in internet technology and digitalization have become solutions for business development and efforts to expand the market. This community service aims to: 1) introduce good MSME business planning and management, and 2) improve MSME business management skills through digital technology. PKM activities were carried out in Motoboi Kecil village, Kotamobagu City. The service is carried out using education and training methods through 1) counseling and development of business management, 2) demonstration of the preparation of business financial statements, and 3) training on digital marketing strategies through social media. The results of the activity showed that the participants' ability to plan and implement the business increased, as well as participants were able to understand and use digital technology, as a means of promoting their products on social media, increasing sales and business profits of MSMEs. Keywords: Digitalization; Internet; Products; Micro-Businesses; Profits